(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Democracy and religions beyond concordat and agreements: towards a participatory declination in relations between the State and religious denominations? Forty years after the Villa Madama agreement, which amended the Lateran Concordat, and the signing of the first agreement pursuant to Article 8, paragraph 3, of the Italian Constitution with the Waldensian Table, it seems necessary to rethink the instruments of dialogue between the State and religious denominations. This contribution proposes the use of legal instruments specific to participatory democracy in order to create a model based on multilateral dialogue between a plurality of religions, all convened by an authority, body or agency of the state, at national or local level, to address issues of common interest. Such a system would complement, but not replace, the current constitutional model and should be framed within a future general law on religious freedom. For the time being, the issues that could already be the subject of this possible dialogue, especially at the local level, are those relating to the construction of places of worship, the protection of religious cultural heritage and the environment, spiritual assistance in hospitals and the teaching of religion in public schools. SOMMARIO: 1. Introduzione: verso nuove forme di bilateralità - 2. Una terza via tra unilateralità e bilateralità: la declinazione partecipativa dei rapporti tra Stato e confessioni religiose - 3. Democrazia partecipativa e religioni: spunti di riflessione a partire dalla questione della sinodalità nella Chiesa cattolica - 4. La spinta europea verso la partecipazione delle religioni: l’art. 17 TFUE - 5. Gli ambiti per la partecipazione delle religioni - 5.1. Nell’urbanistica: nuova edilizia di culto, cambiamenti di destinazione d’uso e riuso - 5.2. Nel patrimonio cultural religioso e nella tutela dell’ambiente - 5.3. Nell’assistenza spirituale nelle strutture sanitarie - 5.4. Nell’insegnamento delle religioni a scuola - 6. Primi spunti e una proposta verso una conclusione quantomai aperta.